Reoxidation of Al-killed ultra-low C steel by FetO in CaO-Al2O3-MgOsat.- FetO slag representing RH slag by experiment and kinetic modelling - Y-M Cho; W-Y Cha; Y-B Kang (The Australasian Institute of Mining and Metallurgy, 2024)
Molten slag used in the secondary refining process (RH process) for the production of Ultra-Low C (ULC) steel is typically composed of CaO-Al2O3-MgOsat.-FetO with minor constituents. FetO in the RH slag is the main source of reoxidation of the molten ULC steel in the ladle by 2Al + 3(FetO) = (Al2O3) + 3Fe, thereby serving as the source of the alumina inclusions. On the other hand, FetO also enhances the fluidity of the slag, thereby increasing inclusion absorption capacity. Optimum slag chemistry design is therefore required to produce clear ULC steel. The reoxidation kinetics was investigated in the present study by employing high-temperature experiments and developing the reaction rate model. Initial compositions of slag ((% CaO)0/(% Al2O3)0 and (% FetO)0)) and reaction temperature were varied and change of [% Al] in the molten steel was measured. The rate-controlling step was analysed. It was found that the rate-controlling step in some cases changed during the reoxidation: from a mass transport of Al in the molten steel to a mixed transport including Al2O3 in the molten slag. The experimental data validated the reaction rate model based on the elucidated reaction mechanism and FactSage thermodynamic database. The model suggested that high (% CaO)0/(% Al2O3)0 suppresses the reoxidation only when (% FetO)0 is low (5 or lower in the present study).